Zakat Fitrah Application based on Web Framework using Waterfall Method - Friyansyah, Karsan; Yanris, Gomal Juni; Muti’ah, Rahma (Politeknik Ganesha Medan, 2022)
Zakat Fitrah is an obligation for every Muslim. In the management of zakat fitrah, the Amil Zakat Agency has a very vital function, namely managing the receipt and distribution of zakat to groups of people who are entitled to receive it (Mustahik). If the amil zakat is negligent and not careful in managing zakat, then the distribution of zakat is not right on target. The Buyung Rahimah Rantauprapat Mosque has the Amil Zakat Fitrah Agency, but in the management process it still uses the manual method so that the zakat management process takes a long time and the data stored is inaccurate. To solve these problems, an orderly, neat and good recording system is needed. This study aims to create an application for the management of Zakat Fitrah at the Buyung Rahimah Rantauprapat Mosque based on the Web Framework. The application development method uses the Waterfall model which divides into four stages, namely: analysis, design, program code generation, and system testing. This research has produced a zakat fitrah application with the main menus, namely: login menu, amil agency, types of zakat, zakat payment, zakat distribution, user management. This application also manages to display zakat fitrah data and zakat fitrah distribution history data. With the application of a web-based framework, making this application user friendly, making it easier for the Amil Agency to manage zakat fitrah. A web framework with the MVC concept and a complete library makes zakat fitrah data management accurate and fast.